Non‐muscle myosin‐IIA is critical for podocyte f‐actin organization, contractility, and attenuation of cell motility. Issue 8 (21st July 2016) - Bondzie, Philip A.; Chen, Hui A.; Cao, Mei Zhen; Tomolonis, Julie A.; He, Fangfang; Pollak, Martin R.; Henderson, Joel M.
Abstract : Several glomerular pathologies resulting from podocyte injury are linked to genetic variation involving the MYH9 gene, which encodes the heavy chain of non‐muscle myosin‐IIA (NM‐IIA). However, the functional role of NM‐IIA has not been studied extensively in podocytes. We hypothesized that NM‐IIA is critical for maintenance of podocyte structure and mechanical function. To test this hypothesis, we studied murine podocytes in vitro subjected to blebbistatin inhibition of NM‐II activity, or RNA interference‐mediated, isoform‐specific ablation of Myh9 gene and protein (NM‐IIA) or its paralog Myh10 gene and protein (NM‐IIB). Using quantitative immunofluorescence microscopy, traction force microscopy, and attachment and "wound healing" assays, we found that NM‐IIA ablation altered podocyte actin cytoskeletal structure and focal adhesion distribution, decreased cell attachment and contractility, and increased cell motility. Blebbistatin treatment had similar effects. NM‐IIB ablation produced cells that exhibited poor attachment, but cytoskeletal structural organization, contractility and motility were maintained. These findings indicate that NM‐IIA is essential for maintenance of podocyte cytoskeletal structure and mechanical function in vitro, and NM‐IIB does not replace it in this role when NM‐IIA expression is altered. We conclude that critical podocyte functions may be affected by MYH9 mutations or disease‐associated haplotypes. © 2016 Wiley Periodicals, Inc.